2022
DOI: 10.3390/genes13030501
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of GABA-Transaminase Gene from Mulberry (Morus multicaulis) and Its Role in Salt Stress Tolerance

Abstract: Gamma-aminobutyric acid (GABA) has been reported to accumulate in plants when subjected to salt stress, and GABA-transaminase (GABA-T) is the main GABA-degrading enzyme in the GABA shunt pathway. So far, the salt tolerance mechanism of the GABA-T gene behind the GABA metabolism remains unclear. In this study, the cDNA (designated MuGABA-T) of GABA-T gene was cloned from mulberry, and our data showed that MuGABA-T protein shares some conserved characteristics with its homologs from several plant species. MuGABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 57 publications
4
7
0
Order By: Relevance
“…In this study, salt stress led to an increase in H 2 O 2 content and a concomitant increase in MDA content in the leaves of ‘Tahe 2’ and ‘Xinluzhong 62’ seedlings. This aligned with previous observations of salt-induced oxidative stress in different plants [ 4 , 14 , 20 , 35 , 36 ]. Under salt stress, compared to the no GABA treatment, treatment with 1~4 mM GABA reduced the H 2 O 2 and malondialdehyde (MDA) content in cotton seedlings, consistent with previous research findings [ 14 , 15 , 20 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, salt stress led to an increase in H 2 O 2 content and a concomitant increase in MDA content in the leaves of ‘Tahe 2’ and ‘Xinluzhong 62’ seedlings. This aligned with previous observations of salt-induced oxidative stress in different plants [ 4 , 14 , 20 , 35 , 36 ]. Under salt stress, compared to the no GABA treatment, treatment with 1~4 mM GABA reduced the H 2 O 2 and malondialdehyde (MDA) content in cotton seedlings, consistent with previous research findings [ 14 , 15 , 20 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…Under salt stress, exogenous GABA treatment increased the activities of SOD and POD in cotton seedlings. This alignment with previous research findings [ 14 , 35 ] further indicated that GABA could alleviate oxidative damage caused by salt stress through direct or indirect mechanisms [ 10 , 11 ]. Interestingly, the impact of exogenous GABA on CAT activity in cotton seedlings of ‘Tahe 2’ and ‘Xinluzhong 62’ under salt stress was the opposite.…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that the GABA-T mutation may prevent GABA degradation, which would affect plants’ ability to grow normally [ 31 ]. In addition, similar to GAD , GABA-T expression is also induced by a variety of stress conditions [ 23 , 25 , 32 ], GABA-T overexpressed plants have been seen to be more sensitive to salt stress in mulberry [ 33 ]. The increase in GABA in the root and above-ground parts of gaba-t seedlings has been seen to be significantly higher than that of the wild type, indicating that the seedling is more sensitive to salt stress than the wild type.…”
Section: Synthesis and Metabolism Of Gabamentioning
confidence: 99%
“…Thus, the study revealed that GABA accumulation under drought stress appears to be involved in stomatal regulation [ 252 ]. Exogenous application of GABA in mulberry resulted in increased antioxidant enzyme activity and decreased oxygen-induced injury associated with increased salt resistance [ 253 ]. In addition, GABA appears to act as a signaling molecule in flooding stress by activating H 2 O 2 signaling and preventing cells from entering programmed cell death (PCD) [ 254 ].…”
Section: Role Of Secondary Metabolites Under Abiotic Stressmentioning
confidence: 99%